Vi er ikke robotter, hvis man kan sige det på den måde. Digressiv køretur gennem Nikolaj Zeuthens flerstrengede fejlbarlighedskunst - Schweppenhäuser, Jakob (Passage - Tidsskrift for litteratur og kritik, 2013)
Jakob Schweppenhäuser fører dette spørgsmål om stemme og lyd videre, når han i “Vi er ikke robotter, hvis man kan sige det på den måde” sætter fokus på sangteksten og dermed forholdet mellem lyrik og musik. Med udgangspunkt i Nikolaj Zeuthen og orkestret Skammens Vogn eksemplificerer Schweppenhäuser, hvordan man kan nærme sig dette felt, ligesom han mere specifikt diskuterer, hvordan spørgsmålet om fejlbarlighed er centralt i Zeuthens virke. Jakob Schweppenhäuser: “We Are Not Robots, so to Speak. Digressive Drive Through the Multipronged Fallible Art of Nikolaj Zeuthen” As a singer, songwriter, comic artist, lyricist, novelist and playwright, Nikolaj Zeuthen has developed a characteristic artistic expression, which formally as well as thematically evokes a fundamental impression of fallibility: He sings out of tune, his comics are slipshod and the human beings who populate his universe struggle with everything from unemployment and receiving disappointing presents to deep and existential doubts and fears. The interrelations in relationships, between family members and between people in general are saturated with awkward, embarrassing, shameful feelings. As the genre of lyrics – in a literary aspect – is strongly underexposed, the article is centered around Zeuthen’s work within the frame of his band, Skammens Vogn: the interplay between words, voice and tones.